ESTRANGEIRO DE MIM: VIAGENS E VIAJANTES - Guimarães, Lívia Cristina (Em Tese, 1998)
This work focuses on travels, and, especially, identities. It is based on a German writer’s descriptions of a trip to Brazil in the 19th century as well as on texts by two Brazilian writes about their visit to Germany in the 20th century. Through experiences and feelings of these so called travellers, diffrences and similarities between Brazilian and German cultures are discussed.